The Role of the Social Dimension of Teachers' Well-Being in Their Collaborative Practices - Hajiyeva, Narmin; Taghizada, Rubaba; Taghizada, Ali; Mutallimova, Gamar (ADA University, 2025)
This qualitative study explores how the social dimension of teachers’ well-being influences their collaborative practices within public secondary schools in Baku, Azerbaijan. It is grounded on Self-Determination Theory (Deci & Ryan, 2008), the Job Demands-Resources Model (Bakker & Demerouti, 2007), and available teacher well-being scholarship, examining participants’ experiences with peers, leadership engagement, trust, and workload challenges. Participants were twelve teachers with a minimum of five years of teaching experience, from whom data were obtained through semistructured interviews, and analyzed according to Braun and Clarke (2006) thematic analysis guidelines. The results highlighted following themes: recognition and belonging, the role of leadership, peer relationships, workload and resource strain, trust and communication, and social well-being and instructional motivation. Findings show that extensive collegial trust, active supportive leadership, and recognition strengthen a collaborative school culture, whereas excessive workloads coupled with scarce resources negatively impact well-being and collaboration. By examining the social aspect of well-being, this study fills the gap in local research and argues that fostering social trust and emotional care among teachers is important for sustained school development and retention of teachers. The outcomes are important to educational administrators and policymakers in Azerbaijan concerning the well-being of teachers and professional community.
Keywords: Teachers -- Job stress -- Azerbaijan -- Psychological aspects.; Teachers -- Professional relationships -- Azerbaijan.; Teacher participation in administration -- Azerbaijan.; Work environment -- Psychological aspects -- Azerbaijan.